Associations between ADHD and emotional problems from childhood to young adulthood: a longitudinal genetically sensitive study. (29th February 2020) - Stern, Adi; Agnew‐Blais, Jessica C.; Danese, Andrea; Fisher, Helen L.; Matthews, Timothy; Polanczyk, Guilherme V.; Wertz, Jasmin; Arseneault, Louise
Abstract : Background: Attention deficit/hyperactivity disorder (ADHD) is associated with emotional problems, and their co‐occurrence often leads to worse outcomes. We investigated the developmental associations between ADHD and emotional problems from childhood to early adolescence and examined the genetic and environmental contributions to their developmental link. We further tested whether this developmental association remained across the transition to young adulthood. Methods: We used data from the Environmental Risk (E‐Risk) Longitudinal Twin Study, a cohort of 2, 232 British twins. In childhood, ADHD and emotional problems were assessed at ages 5, 7, 10 and 12 with mothers' and teachers' reports. At age 18, we used self‐reported symptoms according to DSM‐5 criteria for ADHD, and DSM‐IV for anxiety and depression. Results: Longitudinal analyses showed that earlier ADHD was associated with later emotional problems consistently across childhood. However, earlier emotional problems were not associated with later ADHD symptoms. The developmental association between ADHD and later emotional problems in childhood was entirely explained by common genetic factors. Consistent with results in childhood, earlier symptoms of ADHD were associated with later emotional problems during the transition to young adulthood. Conclusions: Our findings demonstrate that ADHD symptoms are predictors of the development of emotional problems, from childhood up to young adulthood, through shared genetic influences. Interventions targeting ADHD symptoms might prevent the development of emotional problems. Clinicians treating youth with ADHD must be aware of their risk for developing emotional problems and ought to assess, monitor and treat emotional problems alongside ADHD symptoms from childhood to adulthood.